(untitled) (Journal of Hama University, 2024)
The aim of the research was to find out the degree of possession of basic sixth grade students of design thinking skills in the science subject in Banias city.to verify the research objectives, a descriptive curriculum was used. a list of Design Thinking Skills was prepared, and a test of design thinking skills in the science subject. the study sample consisted of (277) students of the basic sixth grade in Banias City Public Schools for the academic year (2022-2023). The following results have been reached: The basic sixth graders’ degree of having design thinking skills in science is moderat. Statistically, there is a difference between the average grade of sixth graders on the test of design thinking skills in the subject of science attributable to the variable of gender, for the benefit of females. Statistically, there is a difference between the average grade of sixth graders on the test of design thinking skills in the subject of science attributable to the variable level of education of parents, for the benefit of pupils from a father and mother with a university degree. Based on the results of the research, it was proposed to enrich science books with scientific activities and educational attitudes that stimulate and develop design thinking skills, and to focus teachers’ attention on raising the level of design thinking among pupils through training and the actual exercise of each of his skills in appropriate classroom situations.